Postoperative cavitating infarction following lobectomy: the importance of variant pulmonary anatomy. Issue 12 (9th December 2020) - Brown, William John Hunter; Masani, Vidan; Batchelor, Tim; Rodrigues, Jonathan C L
Abstract : A 75-year-old woman was admitted to hospital with haemoptysis, fever and shortness of breath. She had undergone a right video-assisted thoracoscopic surgery upper lobectomy for an apical lung cancer 4 weeks earlier, and had been treated with antibiotics for 1 week prior to admission for a suspected postoperative lung abscess. Review of preoperative imaging found that she possessed a lobar pulmonary artery variant, with postoperative imaging confirming that the right lower lobe segmental pulmonary artery had been divided alongside the upper lobe vessels. The diagnosis of a lung abscess was thus revised to a cavitating pulmonary infarct. There are numerous variations of the pulmonary vasculature, all of which have the potential to cause a range of serious vascular complications if not appreciated preoperatively. Measures to mitigate the risk of complications resulting from vascular anomalies should be considered by both radiologists and surgeons, with effective lines of communication essential to safe working.